Hepatitis B virus X protein counteracts high mobility group box 1 protein-mediated epigenetic silencing of covalently closed circular DNA. - Elena S Kim; Jun Zhou; Hu Zhang; Alexander Marchetti; Maarten van de Klundert; Dawei Cai; Xiaoyang Yu; Bidisha Mitra; Yuanjie Liu; Mu Wang; Ulrike Protzer; Haitao Guo (PLoS Pathogens)
Hepatitis B virus (HBV) covalently closed circular DNA (cccDNA), serving as the viral persistence form and transcription template of HBV infection, hijacks host histone and non-histone proteins to form a minichromosome and utilizes posttranslational modifications (PTMs) "histone code" for its transcriptional regulation. HBV X protein (HBx) is known as a cccDNA transcription activator. In this study we established a dual system of the inducible reporter cell lines modelling infection with wildtype (wt) and HBx-null HBV, both secreting HA-tagged HBeAg as a semi-quantitative marker for cccDNA transcription. The cccDNA-bound histone PTM profiling of wt and HBx-null systems, using chromatin immunoprecipitation coupled with quantitative PCR (ChIP-qPCR), confirmed that HBx is essential for maintenance of cccDNA at transcriptionally active state, characterized by active histone PTM markers. Differential proteomics analysis of cccDNA minichromosome established in wt and HBx-null HBV cell lines revealed group-specific hits. One of the hits in HBx-deficient condition was a non-histone host DNA-binding protein high mobility group box 1 (HMGB1). Its elevated association to HBx-null cccDNA was validated by ChIP-qPCR assay in both the HBV stable cell lines and infection systems in vitro. Furthermore, experimental downregulation of HMGB1 in HBx-null HBV inducible and infection models resulted in transcriptional re-activation of the cccDNA minichromosome, accompanied by a switch of the cccDNA-associated histones to euchromatic state with activating histone PTMs landscape and subsequent upregulation of cccDNA transcription. Mechanistically, HBx interacts with HMGB1 and prevents its binding to cccDNA without affecting the steady state level of HMGB1. Taken together, our results suggest that HMGB1 is a novel host restriction factor of HBV cccDNA with epigenetic silencing mechanism, which can be counteracted by viral transcription activator HBx.